CATCHMENT AREA EROSION STUDY IN ESTIMATION OF RESERVOIR CAPACITY AT THE END OF LIFE EXPECTANCY (CASE STUDY : GONDANG RESERVOIR, KARANGANYAR) - Dhanang Samatha Putra (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Gondang Reservoir is one of The National Strategic Projects. Located in Karanganyar Regency, Central Java Province, Gondang Reservoir has 2.08 Mm3 flood storage, 5.03 Mm3 effective storage, 2.03 Mm3 dead storage and 30 years lifetime. In the dam management, one of the problems that often occurs is sedimentation. To overcome this problem, we need to know the sedimentation rate and distribution pattern of Gondang Reservoir for optimalizing the reservoir management. To predict the distribution pattern of the reservoir we use Empirical Area Reduction Methods. The findings of the study show that the sediment volume of the reservoir throughout its effective life is 2,79 Mm3, the new zero elevation is +496 m, there is no remaining dead storage and the remaining effective storage is 2.2 Mm3. This indicates that theoretically the reservoir will work well up to its life expectancy. Dam sedimentation management with structural or non structural must be planned especially at effective storage. Dam sedimentation management at effective storage is very important in order to maintain Gondang Reservoir benefits.